Identifikasi Tingkat Kekompakkan Kota Makassar Berdasarkan Variabel Urban Compactness - Andi Devi Putri Awalina; Ananto Yudoyono; Mimi Arifin (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Makassar City as the largest metropolitan city in the area of East Indonesia encountered continuous population growth rate of 1,32% in 2017. This has an impact on high land demand, resulting in the development of the city outwards which if not well managed will cause urban sprawl problems. Therefore the concept of a compact city emerged as one of the concepts aimed at revitalizing the impact of urban sprawl. This study uses a varitey of analytical techniques that are modified to the purposes which are to identify the level of compactness using quantitaive statistical analysis and scoring analysis, to find out significant factors using multiple linear regression analysis, and to formulate strategies carried out by SWOT analysis. The analysis shows that; 1) the classification of compactness level in Makassar is divided into 4 typologies, 2) population density and ratio of public transport routes simultaneously affect the compactness of Makassar City with 95% detremination rate,3) There are four priority instructions by developing strategies such as transportation adn infrastructure plans, integration and revitalization of city centers, TOD, and mixed use zoning and mixed use building development.